Self-Efficacy, Curiosity, and English Proficiency in EFL Contexts: A Systematic Review and Meta-Analysis (2020–2025) - Susianti Rosalina; Widodo Widodo; Merry Lapasau; Muhammad Anis (FKIP Universitas Lampung, 2026)
English proficiency is critical in English as a Foreign Language (EFL) contexts, yet the psychological and motivational factors influencing learning outcomes require systematic investigation. This meta-analysis synthesizes empirical evidence on the relationships between self-efficacy and English proficiency, curiosity and English proficiency, and self-efficacy and curiosity in EFL contexts, while exploring potential moderators. Following PRISMA 2020 guidelines, this study reviewed 42 Scopus-indexed articles (2020-2025). Data were analyzed using a meta-analysis of correlations with Fisher's Z transformation and a random-effects model. Meta-regression examined the moderating effects of geographic region, respondent type, and sample size. The analysis revealed moderate to strong positive correlations: self-efficacy and English proficiency (r = 0.438, p < 0.001, I² = 87.7%, k = 40 studies), curiosity and English proficiency (r = 0.447, p < 0.001, I² = 63.66%, k = 8 studies), and self-efficacy and curiosity (r = 0.437, p < 0.001, I² = 0%, k = 4 studies). Respondent type emerged as the strongest moderator (Q = 14.82, p < 0.001), with university students showing stronger effects (r = 0.471) than teachers (r = 0.442) and secondary/elementary students (r = 0.365). Geographic region significantly moderated relationships (Q = 9.47, p = 0.024), with Middle Eastern and Asian contexts demonstrating stronger correlations than European contexts. Publication bias was detected (Egger's p = 0.022), indicating underrepresentation of weaker effects. Very high heterogeneity suggests substantial contextual variation. Self-efficacy and curiosity positively correlate with English proficiency, with effects varying by educational level and cultural context. However, findings regarding reciprocal relationships between self-efficacy and curiosity remain tentative due to limitations in the studies. Findings support integrated pedagogical approaches that enhance self-efficacy and exploratory behavior, though the causal mechanisms require further longitudinal and experimental investigation. Keywords: self-efficacy, curiosity, English proficiency, meta-analysis, language learning.